Tropical cyclone influence on the long-term variability of Philippine summer monsoon onset - Hisayuki Kubota; Ryuichi Shirooka; Jun Matsumoto; Esperanza O. Cayanan; Flaviana D. Hilario (Progress in Earth and Planetary Science, 2017)
Abstract The long-term variability of Philippine summer monsoon onset from 1903 to 2013 was investigated. The onset date is defined by daily rainfall data at eight stations in the northwestern Philippines. Summer monsoons tended to start earlier in May after the mid-1990s. Other early onset periods were found during the 1900s, 1920s, and 1930s, and an interdecadal variability of summer monsoon onset was identified. Independent surface wind data observed by ships in the South China Sea (SCS) revealed prevailing westerly wind in May during the early monsoon onset period. To identify atmospheric structures that trigger Philippine summer monsoon onset, we focused on the year 2013, conducting intensive upper-air observations. Tropical cyclone (TC) Yagi traveled northward in the Philippine Sea (PS) in 2013 and triggered the Philippine monsoon onset by intensifying moist low-level southwesterly wind in the southwestern Philippines and intensifying low-level southerly wind after the monsoon onset in the northwestern Philippines. The influence of TC was analyzed by the probability of the existence of TC in the PS and the SCS since 1951, which was found to be significantly correlated with the Philippine summer monsoon onset date. After the mid-1990s, early monsoon onset was influenced by active TC formation in the PS and the SCS. However, the role of TC activity decreased during the late summer monsoon periods. In general, it was found that TC activity in the PS and the SCS plays a key role in initiating Philippine summer monsoon onset.